EFA: A Viable Alternative to RDMA over InfiniBand for DBMSs? - Ziegler, Tobias; Bindiganavile Mohan, Dwarakanandan; Leis, Viktor; Binnig, Carsten (18th International Workshop on Data Management on New Hardware, DaMoN 2022, 2022)
RDMA over InfiniBand offers high bandwidth and low latency which provides many benefits for distributed DBMSs. However, in the cloud RDMA is still not widely available. Instead, cloud providers often invest in their own high-speed networking technology and start to expose their own native networking interfaces. For example, the largest cloud provider, Amazon Web Services (AWS), introduced instances with Elastic Fabric Adapter (EFA) in 2018. In this paper, we aim to analyze EFA as an alternative to RDMA in the cloud by performing an in-depth and systematic evaluation.
CRIS-Team Scopus Importer:2022-07-15